Fabrication of antibacterial chitosan/PVA nanofibers co-loaded with curcumin and cefadroxil for wound healing - Rashid Saman; Waqas Muhammad Khurram; Tahir Ayesha; Yasin Haya; Nasir Bushra; Khan Abida Kalsoom; Ijaz Munaza; Murtaza Ghulam (Green Processing and Synthesis)
This study aimed to prepare chitosan/PVA nanofibers loaded with cefadroxil and curcumin (CPCCNFs) by electrospinning. According to FTIR spectra, there was no interaction between drugs and polymers. X-ray diffractograms showed the amorphous nature of cefadroxil and curcumin in its nanofiber form. According to thermogravimetric analysis results, CPCCNFs remained thermally stable up to 423°C. CPCCNFs exhibited an initial swelling ratio of 80.76% and an erosion rate of 44.2%, indicating a good liquid absorption capacity. Dissolution tests showed an initial burst release of 75% of the drug within the first hour, followed by the sustained release over 2 h. The zeta potential of CPCCNFs ranged from −9.6 to +11.1 mV, confirming good colloidal stability. The antibacterial results showed an appreciable zone of inhibition of 14.6 ± 1.0 mm against Staphylococcus aureus, demonstrating the strong antibacterial potential of CPCCNFs. According to wound closure and histopathological studies, CPCCNF-treated wounds exhibited a 60% reduction by day 3, 72% by day 7, 85% by day 14, and complete closure by day 19, significantly outperforming the positive control (Quench) and negative control (untreated). The characterizations confirmed the successful synthesis of stable CPCCNFs with good antibacterial potential against Gram-positive bacteria and a promising wound healing ability.